1978
DOI: 10.1139/z78-067
|View full text |Cite
|
Sign up to set email alerts
|

Integumentary bloodvascular system in garter snakes (Thamnophis sirtalis parietalis and Thamnophis radix)

Abstract: Integumentary arteries in garter snakes are a continuation of intercostal arteries. They give rise to a complex network of conduits resembling in pattern the outline of scutes. The arrangement of integumentary veins approximates that for arteries; venous drainage occurs ventrally via the epigastric vein, and laterally via intercostal and spinal veins. The return of blood via this latter route during basking is presumably associated with convective heat transfer to the spinal cord enhancing the potential speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, vertebrate pheromones are not necessarily of glandular origin; urine and feces, for example, may contain pheromonal substances (Muller-Schwarze and Moze11, 1977). Thus, when we learned of a specialized network of blood vessels in the skin of Thamnophis snakes (Rauch, 1978),we hypothesized that the circulation could be the source of the pheromone. Although in retrospect it seems obvious that the skin would have a blood supply, and others had discussed it (White, 1957), Rauch's description served as a catalyst for our thinking.…”
Section: Nature and Source Of The Pheromonementioning
confidence: 99%
See 3 more Smart Citations
“…However, vertebrate pheromones are not necessarily of glandular origin; urine and feces, for example, may contain pheromonal substances (Muller-Schwarze and Moze11, 1977). Thus, when we learned of a specialized network of blood vessels in the skin of Thamnophis snakes (Rauch, 1978),we hypothesized that the circulation could be the source of the pheromone. Although in retrospect it seems obvious that the skin would have a blood supply, and others had discussed it (White, 1957), Rauch's description served as a catalyst for our thinking.…”
Section: Nature and Source Of The Pheromonementioning
confidence: 99%
“…Although in retrospect it seems obvious that the skin would have a blood supply, and others had discussed it (White, 1957), Rauch's description served as a catalyst for our thinking. We reasoned that if the pheromone was present in the circulation it might reach the skin via Rauch's (1978) vessels and percolate out through the skin. The implications of this hypothesis are: 1) the pheromone, or a precursor of it, will be found in the blood, 2) some internal organ in the body will be the site of pheromone synthesis, 3) some process in the skin or at the level of the skin will be responsible for pheromone release onto the skin surface, and 4) either males produce pheromone with male skin limiting its release, or male skin is fundamentally like female skin, but males do not produce pheromone.…”
Section: Nature and Source Of The Pheromonementioning
confidence: 99%
See 2 more Smart Citations
“…Further, estrous females whose skin is coated with petroleum jelly are not courted (Noble, 1937). Rauch (1978) has hypothesized that in Thamnophis, only female skin is structured in such a manner so as to allow blood-borne pheromones to be secreted. However, Garstka (1982) showed that male and female skin structure in…”
mentioning
confidence: 99%